An Evaluation of Marital Conflict Resolution in Egor Local Government Area, Edo State, Nigeria - Egharevba, Osagie Joseph; Omosuvbe, Joy Iziegbuwa (NIU Journal of Social Sciences, 2024)
Marriage is a life-long commitment where the couple endures a variety of challenging circumstances, including illness, financial hardship, crises, and so forth. As an age-old institution, marriage is supposed to be an exciting and beautiful adventure, and the relationship between husband and wife is intended to get better with every passing day or year, but in reality, many challenges can mar the relationship. The study therefore examines an evaluation of marital conflict resolution in Egor Local Government Area, Edo State, Nigeria. The descriptive survey research design was adopted for the study. The study adopted a triangulation of both the quantitative and qualitative method of data collection. The area of study was Egor Local Government Area, Edo State, Nigeria. The population of study consisted of both Literate and non-literate males and females from 18years and above in the study area. The sample size was 396 respondents. Each variable was analyzed descriptively using number and percentages for each of the independent variables. The variables were cross tabulated between major and sub cartegories and tested with appropriate standardized statistical tools. The findings revealed that there are a lot of predisposing factors that trigger marital dissolution among couples in the study area, but few of them were identified. It was also recommended that premarital counseling is necessary for prospective couples to better understand one another before marriage. Couples should regularly attend seminars and workshops on topics related to marital harmony and conflict resolution. The study recommended that the use of uncensored languages should not be used among couples. The study also recommended that there should be the need of premarital counseling among couples Keywords: Conflict, Divorce, Family, Mariage, Resolutions.